2010
DOI: 10.1179/174313209x459084
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional outcomes of laminoplasty and laminectomy

Abstract: Both cervical laminectomy and laminoplasty are safe and effective for the treatment of cervical myelopathy or radiculopathy. Cervical laminoplasty results in a shorter hospital stay and greater functional improvement at 4 months follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…The characteristics of the included studies are summarized in Table 1. Among the studies, LAMP surgical procedures mainly refer to open-door laminoplasty with different fixation, while LAMT surgical procedures were divided into three subgroups as follows: conventional LAMT [6-8,11,13,18], skip LAMT [10,12,14], and LAMT with fusion [9,15-17,19,20]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are summarized in Table 1. Among the studies, LAMP surgical procedures mainly refer to open-door laminoplasty with different fixation, while LAMT surgical procedures were divided into three subgroups as follows: conventional LAMT [6-8,11,13,18], skip LAMT [10,12,14], and LAMT with fusion [9,15-17,19,20]. …”
Section: Resultsmentioning
confidence: 99%
“…In four studies [10,11,16,20], C5 paresis was found in 9 of 176 (5.11%) patients treated with LAMP and 12 of 157 (7.64%) patients treated with LAMT. Across six studies [9,13-16,20], infection was found in 4 of 254 (1.57%) patients treated with LAMP and 10 of 261 (3.83%) patients treated with LAMT. There was no significant difference between the two techniques in the incidence of kyphosis, C5 paresis, or infection ( P  > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Both laminectomy and laminoplasty are safe and effective treatments for cervical myelopathy [4,5,14]. As laminoplasty is less destructive to posterior tissues than laminectomy, the more opportunity for muscles to be reattached to bone and the more preservation of bony covering of the dura mater in laminoplasty may contribute to less postoperative axial pain.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent longterm results have been reported using this technique [3][4][5][6][7]. Clinical follow-up studies have shown that laminoplasty generally results in greater patient satisfaction and lower complication rates than laminectomy [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%